2002
DOI: 10.1021/ja025796b
|View full text |Cite
|
Sign up to set email alerts
|

Isotactic-b-Syndiotactic Stereoblock Poly(methyl methacrylate) by Chiral Metallocene/Lewis Acid Hybrid Catalysts

Abstract: Stereoblock polymerization with chiral ansa-metallocene/strong Lewis acid hybrid catalysts capable of switching stereospecificity of the methyl methacrylate polymerization produces the highly stereoregular isotactic-b-syndiotactic stereoblock poly(methyl methacrylate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 23 publications
4
50
0
2
Order By: Relevance
“…The glass transition temperatures (T g ) of extracted PMMA, determined from the mid-point of the glass transition in the heat flow curves (vide infra), were observed between 98 and 100°C from both polymerized emulsion and emulsion gel samples. These T g 's are in consistent with the observations for the PMMA with similar tacticities [17,33]. The glass transition was primarily a reversing transition: the intensity of the reversing heat flow was much larger than that of the non-reversing heat flow.…”
Section: Thermal Analysissupporting
confidence: 88%
“…The glass transition temperatures (T g ) of extracted PMMA, determined from the mid-point of the glass transition in the heat flow curves (vide infra), were observed between 98 and 100°C from both polymerized emulsion and emulsion gel samples. These T g 's are in consistent with the observations for the PMMA with similar tacticities [17,33]. The glass transition was primarily a reversing transition: the intensity of the reversing heat flow was much larger than that of the non-reversing heat flow.…”
Section: Thermal Analysissupporting
confidence: 88%
“…The switching of growing polymer chain from the isospecific, cationic Zr site to the syndioselective, anionic Al site was demonstrated by the successful synthesis of highly stereoregular isotactic‐ b ‐syndiotactic stereodiblock PMMA (Scheme ) 18. In this sequential polymerization, the first portion of MMA was polymerized with rac ‐(EBI)ZrMe + MeB(C 6 F 5 ) 3 to an isotactic block via the living isospecific, cationic zirconocene enolate propagating species E .…”
Section: Diastereospecific Polymerization By Zirconocenium Cation–enomentioning
confidence: 99%
“…Chen et al showed that stereoregularity greatly depends on co-catalysts: 44 and 46 with borane give isotactic poly(MMA) by catalytic-site control, while these catalysts with the alane Al(C 6 F 5 ) 3 give syndio-rich poly(MMA) by chainend control [144]. They achieved iso-b-syndio stereoblock poly(MMA) using the borane and the alane in one pot [145].…”
Section: Group 4 Metallocenesmentioning
confidence: 99%